The Silent Tarekat in Islamic Law: Legal Consciousness and the Chishti Sufi Legacy of the Tablighi Jamaat - Anshori, Ahmad Yani; Abdurrahman, Landy Trisna; Tamtowi, Moh.; Musaffa, Muhamad Ulul Albab (Universitas Islam Negeri Jakarta, 2025)
This article explores the silent legal and spiritual framework of the Tablighi Jamaat (TJ) in Indonesia, drawing on fieldwork, interviews, and textual analysis. While TJ does not claim to be a Sufi order (ṭarīqah), its practices suggest a reconfiguration of the Chishti-Ḥanafī legacy within a non-institutional framework. The study argues that TJ operates as a